Optimum weighbridge locations in container terminals. Issue 2 (4th June 2019) - Keceli, Yavuz; Oguz, Mehmet
Weighing of containers is an important task in container terminals, and can lead to operational bottlenecks if it causes long queues. This study develops a simulation model to compare different container terminal layouts in terms of weighbridge location. The results indicate that when weighbridges are located at the gates rather than inside the terminal area, this causes shorter queues and leads to shorter truck turnaround times.